Semi-quantification of renal perfusion using 99mTc-DTPA in systolic heart failure: a feasibility study - Ma, Haifang; Gao, Xian; Yin, Pei; Zhao, Qingzhen; Zhen, Yuzhi; Wang, Yu; Liu, Kunshen; Liu, Chao (Annals of nuclear medicine, 2021)
Background Renal scintigraphy with 99m Tc-diethylenetriaminepentaacetic acid (DTPA) may be used to study renal perfusion (RP) in heart failure (HF) patients. The goal of this study was to establish a new method to assess RP in patients with systolic HF. Methods In this retrospective, single-center, observational study, 86 subjects with left ventricular ejection fraction ≤ 45% and 31 age-matched subjects without HF underwent renal scintigraphy with 99m Tc-DTPA. Patients with HF were classified into two categories according to the New York Heart Association (NYHA) functional class, i.e., moderate HF with NYHA functional class I or II and severe HF with NYHA functional class III or IV. The first-pass time-activity curve of the renal scintigraph was recorded. The GFR was determined by Gates' method. The time to peak perfusion activity ( T p ), the slope of the perfusion phase ( S p ), the slope of the washout phase ( S w ), and glomerular filtration rate (GFR) in the study were obtained. Differences between groups were assessed by one-way analysis of variance with the Bonferroni post hoc test and rank-sum test. Results RP in HF was impaired despite comparable GFRs between the control and HF groups. RP in HF was characterized by a longer T p and a shallower S p and S w . The primary parameter ( T p ) was significantly prolonged in patients with HF (41.63 ± 12.22 s in severe HF vs. 26.95 ± 6.26 s in moderate HF vs. 17.84 ± 3.17 s in control, P < 0.001). At a cutoff point of 22 s, there was a high sensitivity (0.895) and specificity (0.935) in identifying patients with HF. Conclusions Renal scintigraphy with 99m Tc-DTPA may represent a new and useful method to noninvasively monitor RP abnormalities in HF.